PENGARUH PENGANGGURAN DAN INFLASI TERHADAP PRODUK DOMESTIK BRUTO INDONESIA TAHUN 2009-2019 - Sri Harjunawati; Ida Hendarsih (STKIP PGRI SITUBONDO, 2020)
In accordance with article 33 of the 1945 Constitution, the main objective of the Indonesian government is the prosperity of the Indonesian people. The state is said to be prosperous if most of the needs of its people are met. Satisfaction needs in the form of goods and services produced in the territory of Indonesia, namely Gross Domestic Revenue. There are many aggregative factors that influence the Gross Domestic Product, including Unemployment and Inflation. This study examines the effect of unemployment and inflation on the Gross Domestic Product. Research on the influence of the Unemployment independent variable (X1) on Gross Domestic Product (Y) produces at-value of -4,974> 2,300 (t table). Research on the influence of the Inflation (X2) independent variable on the dependent variable of the Gross Domestic Product yields a calculated value of -1,511 <2,300 (t table). Multiple linear tests in this study produced a calculated F value of 14,834> 4.35 (F table). The regression equation in this study is Y = 21036872.292 - 1.526 X1 - 127482.199X2 + e. R-value of the correlation coefficient of 0.900 and R square value of 0.809.